Canaux anciens et puits récents : usages de l’eau d’irrigation, identité et territoire dans le Haouz (Maroc) - Violaine Héritier-Salama (Développement Durable et Territoires, 2019)
By associating an ethnography of contemporary practices and a diachronic approach, this article tries to show the co-construction over time of an irrigated soil and of a social group, in a locality in Marrakesh’s plain (Haouz). The technical, political and economical issues of a long-term hydrosocial cycle as much as the daily practices enlighten the inception of convergent interests for independent farmers. They shape a particular locality characterised by an innovative conversion in horticultural productions. The contrasted use of two technical objects, ancient channels and new motorized wells, leads to the social production of two sorts of water. Each sort allows to manage hazard and to experiment different kinds of collectives in a proper way, while modelling a common identity.